Efektivitas Permainan Edukatif Edupearl Board Terhadap Perkembangan Kognitif Usia 5-6 Tahun - Dini Putri Pratiwi; Deni Widjayatri (Universitas Muhammadiyah Gresik, 2024)
Cognitive development is closely related to an individual's knowledge and their way of processing information regarding situations, actions, and things observed in their surroundings. This research aims to evaluate the effectiveness of the EduPearl Board as an educational play tool on the cognitive abilities of children at TK Istiqomah in Kota Cilegon. The research method utilized was qualitative, employing data collection techniques through observation and documentation. The research participants consisted of 17 children aged 5-6 years old at TK Istiqomah in Kota Cilegon. The research findings indicate that the EduPearl Board game is effective in enhancing the cognitive abilities of 5-6-year-old children, with all children receiving an assessment of 'very good'. Consequently, the conclusion drawn is that the EduPearl Board game is capable of improving the cognitive development of 5-6- year-old children, as evidenced by the highly positive assessments obtained from the research.